Yeast precursor mRNA processing protein PRP19 associates with the spliceosome concomitant with or just after dissociation of U4 small nuclear RNA. - Tarn, W Y (1993)
During assembly of the spliceosome, the U4 small nuclear RNA (snRNA) interacts with the spliceosome as a preformed U4/U6-U5 triple small nuclear ribonucleoprotein (snRNP) complex. Subsequently, U4 becomes loosely associated with the spliceosome, whereas U5 and U6 remain tightly associated, suggesting unwinding of the U4/U6 duplex. We show that this step of the assembly process can be blocked by limiting the ATP concentration in the splicing reaction. We also show that the yeast precursor mRNA processing protein PRP19 becomes associated with the spliceosome during this transition. Thus, PRP19 may function in this step of spliceosome assembly.